INDONESIAN CULTURAL DIPLOMACY IN THE INDONESIA-THAILAND CULTURAL EXCHANGE PROGRAM 2023 EVENT - Siregar, Ahmad Farhan; Indrawati (Universitas prof. Dr. Moestopo (Beragama), 2024)
Cultural diplomacy plays an important role in strengthening international relations and enhancing mutual understanding between countries. The Indonesian Embassy in Bangkok organizes the 2023 Indonesia-Thailand Cultural Exchange Program, an important initiative to promote Indonesian culture in Thailand. This research examines the impact and effectiveness of cultural diplomacy through this exchange program. The research employs qualitative methods, emphasizing content analysis, to gather and classify significant contexts. Primary data were collected through interviews resource persons at the Indonesia Embassy in Bangkok and participants of the 2023 Indonesia-Thailand Cultural Exchange Program, and also utilizes secondary data from Instagram @IndonesiainBangkok. The results of this research show that cultural diplomacy, facilitated by initiatives such as the Indonesia-Thailand Cultural Exchange Program, can contribute to improving bilateral relations and strengthening appreciation of cultural diversity. This research underlines the importance of cultural diplomacy in achieving diplomatic goals, fostering mutual understanding and strengthening people-to-people connections between Indonesia and Thailand.